Pengaruh Kunjungan Rumah oleh Bidan terhadap Peningkatan Pengetahuan Ibu tentang Perawatan Bayi Baru Lahir - Putri Diah Pemiliana; Novitri Adelina Sipayung (Inovasi Kesehatan Global, 2024)
Midwife home visits are a form of healthcare service aimed at enhancing mothers' knowledge of newborn care. This study aims to analyze the impact of midwife home visits on improving mothers' knowledge of newborn care. The research employed a quantitative method with a quasi-experimental design. The sample consisted of 60 new mothers, divided into intervention and control groups. The study's findings indicated a significant increase in the knowledge of mothers in the intervention group compared to the control group after the midwife home visits. The home visits were proven effective in improving mothers' understanding of newborn care, including exclusive breastfeeding, umbilical cord care, and recognizing danger signs in newborns.